1957
DOI: 10.1111/j.1476-5381.1957.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition by Sodium Salicylate of Oedema of the Hind‐paw of the Rat Induced by 5‐hydroxytryptamine

Abstract: The subcutaneous administration of 600 mg./kg. body weight of sodium salicylate to adult rats 3 to 4 hr. previously inhibited the development of hind-paw oedema following the injection of 2.5 ,ug. of 5-hydroxytryptamine. This effect was more pronounced in normal than in adrenalectomized rats.The inhibitory effect of large doses of salicylate on rat hind-paw oedema induced with testicular extract has been previously described (Kelemen, Majoros, Ivanyi, and Kovacs, 1950 (1956). A dose of 0.5 to 1.0 pg. was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1957
1957
1983
1983

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The results shown in Table 3 indicate that sodium salicylate is capable of inhibiting the capillary hyperpermeability produced by the intradermal injection of histamine. The fact that sodium salicylate was considerably less active in the adrenalectomized animal recalls the observation of Keleman (1957) that sodium salicylate was less active in the adrenalectomized rat than in the intact animal in antagonizing the oedema of the rat foot in response to an injection of 5-hydroxytryptamine.…”
Section: Resultsmentioning
confidence: 96%
“…The results shown in Table 3 indicate that sodium salicylate is capable of inhibiting the capillary hyperpermeability produced by the intradermal injection of histamine. The fact that sodium salicylate was considerably less active in the adrenalectomized animal recalls the observation of Keleman (1957) that sodium salicylate was less active in the adrenalectomized rat than in the intact animal in antagonizing the oedema of the rat foot in response to an injection of 5-hydroxytryptamine.…”
Section: Resultsmentioning
confidence: 96%
“…It has long been recognized that sodium salicylate has a cortisone-like effect, but it has been shown that in man this is not due to an increase in the plasma level of adrenal cortical hormone (Bayliss and Steinbeck, 1954). Kelemen (1957) has shown that salicylate antagonizes the oedema of the paw in the rat produced by locally injected 5-HT in the intact but not in the adrenalectomized animal. This suggests that salicylates depend in some way on the adrenal corticoids for some of their actions, and it seems likely that a similar synergism plays a part in the antagonism of the vascular effects of 5-HT in man.…”
Section: Methodsmentioning
confidence: 99%
“…In the present paper a comparison is made of the antagonistic effect on these responses of 2-bromo-( + )-lysergic acid diethylamide bitartrate (BOL 148) with that of sodium salicylate, which has been shown by Kelemen (1957) to diminish the oedema of the paw of the rat produced by locally injected 5-HT.…”
mentioning
confidence: 99%
“…In the doses which were active against formaldehyde none of these compounds showed any activity against 5-hydroxytryptamine. Keleman (1957) found that salicylate in doses of 600 mg/kg reduces 5-hydroxytryptamine-induced inflammation in the rat foot, but the doses which he used were considerably greater than those used by us.…”
Section: Resultsmentioning
confidence: 99%